Family Roles and Support in Preventing Stunting: A Systematic Review - Nur Alam Fajar; Mohammad Zulkarnain; Ridha Taqwa; Kiki Sulaningsi; Esti Sri Ananingsih; Riris Diana Rachmayanti; Siau Ching Sin (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2024)
Background: Stunting is inadequacy in physical growth. Stunting can be detrimental to children under five as it causes low intelligence, decreased endurance, and inhibited growth and development. This will increase risk of infections and non-communicable diseases in adulthood. The optimal implementation of family roles supports the improvement of nutritional status in toddlers so it can reduce the incidence of stunting.Method: This systematic review is written in accordance to the PRISMA guidelines. The process includes analysis on online articles from databases of ScienceDirect, PubMed, and Google Scholar for the past five years the period from 2019 with the keywords